Effects of intracerebral neurotrophic factor application on motor symptoms in Parkinson's disease: A systematic review and meta-analysis. (May 2017) - Hegarty, Shane V.; Lee, David J.; O'Keeffe, Gerard W.; Sullivan, Aideen M.
Abstract: Introduction: Neurotrophic factors (NTFs) have been evaluated for neuroprotective effects in Parkinson's disease (PD). However, clinical trials examining the efficacy of intracerebral administration of NTFs on motor symptoms in PD have produced mixed results, and are thus inconclusive. The objective of this systematic review and meta-analysis was to determine the effects of intracerebral NTF application on motor symptoms in people with PD. Methods: We searched PubMed, MEDLINE, EMBASE, and Cochrane from inception through to March 31 2016 for open-label trials and randomized controlled trials (RCTs) which intracerebrally administered NTFs to PD patients, and which performed motor examination using the Unified Parkinson's Disease Rating Scale. Results: Eight studies with a total of 223 participants were included. Fixed effects analysis revealed that NTF treatment did not significantly reduce motor symptoms in PD patients compared to placebo controls (P = 0.98). Combining open-label and RCT data, both treatment with NTFs (P < 0.001) and treatment with placebo (P < 0.05) significantly improved motor function in PD patients when compared to predicted symptoms in untreated PD controls. Finally, random effects analysis revealed that NTF-treated PD patients were not significantly likely to improve following intracerebral NTF administration (P = 0.25). Conclusion: In conclusion, intracerebral NTF administration does not improve motor symptoms in PD patients, when compared to placebo-treated controls. These findings may guide therapeutic decisions and inform future research on NTFs and their application in PD. Highlights: Intracranial neurotrophic factor application did not reduce motor symptoms in PD. NTFs and placebo improved UPDRS scores in PD over predicted scores in untreated PD. PD motor symptoms are not likely to improve after intracranial application of NTFs. Further studies are critical to advance the therapeutic application of NTFs for PD.